2014
DOI: 10.1111/bij.12213
|View full text |Cite
|
Sign up to set email alerts
|

Wheat curl mite and dry bulb mite: untangling a taxonomic conundrum through a multidisciplinary approach

Abstract: Two economically important eriophyoid mites, Aceria tosichella (wheat curl mite; WCM) and Aceria tulipae (dry bulb mite; DBM), were frequently confounded in the world literature until the late 20th Century. Their morphological similarity and ambiguous data from plant‐transfer and virus‐transmission trials contributed to this confusion. Until recently, there was a general lack of knowledge about the existence of species complexes and it was not possible to accurately genotype tested mites. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 62 publications
3
35
2
Order By: Relevance
“…Indeed, the tiny size and structural simplicity of eriophyoid mites hinder their taxonomic identification and differentiation between morphologically related species [46]. Recently, advents in DNA barcoding have been successfully employed in studies of eriophyoid mites and led to discovery of many morphologically cryptic species with inter-species divergence in mtDNA COI ranging from 11% to 28% [36, 47]. Genetic analyses showed that white and red felt galls contained different genotypes of A .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the tiny size and structural simplicity of eriophyoid mites hinder their taxonomic identification and differentiation between morphologically related species [46]. Recently, advents in DNA barcoding have been successfully employed in studies of eriophyoid mites and led to discovery of many morphologically cryptic species with inter-species divergence in mtDNA COI ranging from 11% to 28% [36, 47]. Genetic analyses showed that white and red felt galls contained different genotypes of A .…”
Section: Discussionmentioning
confidence: 99%
“…Primers for PCR amplification and sequencing are shown in Table 2 (Skoracka and Dabert 2010;Skoracka et al 2012Skoracka et al , 2014Bouneb et al 2014) were added to the original dataset (Abacarus hystrix, gi_237513198; Aceria eximia, gi_126009698; Aceria tosichella, gi_337271927; Aceria tulipae, gi_237513230; Aculodes mckenziei, gi_237513226; Trisetacus juniperinus sensu K., gi_403233994).…”
Section: Dna Extraction Amplification Of Dna Fragments and Sequencingmentioning
confidence: 99%
“…This DNA marker has been utilized successfully in phylogenetic studies at the species level and has been proposed as a DNA bar code for taxonomic differentiation of animal species (Sonnenberg et al 2007). This DNA fragment has also been successfully applied to the delimitation of species (including cryptic species) in eriophyoid mites (e.g., Skoracka et al 2013Skoracka et al , 2014Lewandowski et al 2014). No variability between obtained sequences was detected.…”
Section: Resultsmentioning
confidence: 99%